Les fortunes du serment d’allégeance à l’heure du mercantilisme et du « retour » des Juifs en Angleterre (1606-1753) - Frédéric Herrmann (Etudes Epistémè)
This paper looks into the role assigned to the oath of allegiance in the relationship between the Crown and the Jewish community that settled in Great Britain in the 17th and 18th centuries. It focuses on the use of the oath in the process of naturalisation. A study of naturalisation cases not only reveals that the Christological oath was totally inadequate as regards the Jews, but also that the modern state proved to be inventive and flexible in the redefinition of rules, following a very obvious mercantilist policy. The fact that the Sephardic Jews who had to undergo those tests were Marranos shows even more the practical limitations of the oath of allegiance, since, during their past experience in Spanish and Portuguese territories, they both concealed their conscience and feigned their allegiance. The theologico-political oath before God is no longer a warrant of order and obedience.